Pendugaan Umur Simpan Roti Sourdough Bekatul Menggunakan Metode ASLT dengan Pendekatan Arrhenius - Rachma Yayank Moeztamy; Ardhia Deasy Rosita Dewi; Yayon Pamula Mukti (Keluwih: Jurnal Sains dan Teknologi, 2023)
Abstract—Sourdough bread is a type of bread made with sourdough containing a consortium of Lactobacillus spp bacteria and yeast from the fermentation of flour and water for approximately 7 days. Rice bran sourdough bread was chosen because of its nutritional content, namely protein, fat, carbohydrates, crude fiber, calories and is rich in B vitamins, especially vitamin B1 (thiamin). Rice bran sourdough bread is a functional bakery product that is expected to have a longer shelf life than bread in general. The aim of this research is to determine the shelf life of bran sourdough bread with various types of packaging, namely vacuum and plastic packaging. The method used is the Accelerated Shelf-Life Test (ASLT) method with test parameters used including color test, water activity test, Total Plate Number (ALT) test. The test results showed that on the 8th day, 50% of panelists rejected the bran sourdough bread. The test parameter that has the lowest critical activity energy (EA) value for determining the shelf life of rice bran sourdough bread is the bacterial contaminant test. Based on these results, the EA parameter the bacterial contaminant determines the Arrhenius equation calculation formula for the shelf life of rice bran sourdough bread. The results of calculating the shelf life of rice bran sourdough bread in vacuum packaging at temperatures of 32°C, 42°C and 52°C are 10.2; 8.88; 7.79 days, while in plastic packaging at temperatures of 32°C, 42°C and 52°C it is 8.3; 7.64; 7.07 days. Unpackaged bran sourdough bread at temperatures of 32°C, 42°C, and 52°C, namely 1.57; 1.23; 0.98 days. Rice bran sourdough bread packaged in vacuum plastic has a longer shelf life compared to sourdough bread without the addition of rice bran. Keywords: sourdough bread, rice bran flour, arrhenius, shelf life, vacuum Abstrak—Roti sourdough merupakan jenis roti yang dibuat dengan adonan asam yang berisi konsorsium bakteri Lactobacillus spp. dan ragi dari hasil fermentasi tepung terigu dan air selama kurang lebih 7 hari. Roti sourdough bekatul dipilih karena kandungan zat gizi yang dimiliki oleh bekatul yaitu protein, lemak, karbohidrat, serat kasar, kalori serta kaya akan vitamin B, terutama vitamin B1 (thiamin). Roti sourdough bekatul merupakan produk bakery fungsional yang diharapkan memiliki umur simpan lebih lama dari roti pada umumnya. Tujuan penelitian ini adalah mengetahui umur simpan roti sourdough bekatul dengan variasi jenis kemasan yaitu dikemas vakum dan plastik. Metode yang digunakan adalah metode Accelerated Shelf-Life Test (ASLT) dengan parameter uji yang digunakan meliputi uji warna, uji aktivitas air, uji jumlah kontaminan menggunakan Angka Lempeng Total (ALT). Hasil uji menunjukkan pada hari ke-8, roti sourdough bekatul mengalami penolakan panelis sebanyak 50%. Parameter uji yang memiliki nilai energi aktivitasi terendah (EA) kritis mutu untuk penentuan umur simpan roti sourdough bekatul adalah uji kontaminan bakteri. Berdasarkan hasil tersebut, EA parameter kontaminan bakteri menjadi penentu rumus perhitungan persamaan Arrhenius untuk umur simpan roti sourdough bekatul. Hasil perhitungan umur simpan roti sourdough bekatul pada kemasan vakum pada suhu 32°C, 42°C, dan 52°C yaitu 10,2; 8,88; 7,79 hari, sedangkan pada kemasan plastik pada suhu 32°C, 42°C, dan 52°C yaitu 8,3; 7,64; 7,07 hari. Roti sourdough bekatul tanpa dikemas pada suhu 32°C, 42°C, dan 52°C yaitu 1,57; 1,23; 0,98 hari. Roti sourdough bekatul dengan dikemas plastic vakum memiliki umur simpan lebih lama dibandingkan dengan roti sourdough tanpa penambahan bekatul. Kata Kunci: roti sourdough, tepung bekatul, arrhenius, umur simpan, vakum